2019
DOI: 10.1002/ijgo.12880
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile cystic adenomyoma mimicking a Mullerian uterine anomaly successfully treated by laparoscopic excision

Abstract: A 14‐year‐old patient diagnosed with a juvenile cystic adenomyoma mimicking a Mullerian uterine anomaly successfully treated by a laparoscopic excision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 3 publications
2
16
0
Order By: Relevance
“…The authors reported complete resolution of the cyst associated with symptomatic relief (Nabeshima et al, 2008). Following this report, many other authors reported successful laparoscopic management of such cases (Dadhwal et al, 2017;Kriplani et al, 2011;Takeuchi et al, 2010;Ball et al, 2009;Takeda et al, 2007;Jain and Goel 2012;Strelec et al, 2019;Deblaere et al, 2019). The technique of laparoscopic excision of JCA in case 1 and case 3 of our series is similar to the techniques described by other investigators (Dadhwal et al, 2017;Kriplani et al, 2011;Takeuchi et al, 2010;Ball et al, 2009;Takeda et al, 2007;Jain and Goel, 2012;Strelec et al, 2019;Deblaere et al, 2019).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The authors reported complete resolution of the cyst associated with symptomatic relief (Nabeshima et al, 2008). Following this report, many other authors reported successful laparoscopic management of such cases (Dadhwal et al, 2017;Kriplani et al, 2011;Takeuchi et al, 2010;Ball et al, 2009;Takeda et al, 2007;Jain and Goel 2012;Strelec et al, 2019;Deblaere et al, 2019). The technique of laparoscopic excision of JCA in case 1 and case 3 of our series is similar to the techniques described by other investigators (Dadhwal et al, 2017;Kriplani et al, 2011;Takeuchi et al, 2010;Ball et al, 2009;Takeda et al, 2007;Jain and Goel, 2012;Strelec et al, 2019;Deblaere et al, 2019).…”
Section: Discussionsupporting
confidence: 79%
“…Following this report, many other authors reported successful laparoscopic management of such cases (Dadhwal et al, 2017;Kriplani et al, 2011;Takeuchi et al, 2010;Ball et al, 2009;Takeda et al, 2007;Jain and Goel 2012;Strelec et al, 2019;Deblaere et al, 2019). The technique of laparoscopic excision of JCA in case 1 and case 3 of our series is similar to the techniques described by other investigators (Dadhwal et al, 2017;Kriplani et al, 2011;Takeuchi et al, 2010;Ball et al, 2009;Takeda et al, 2007;Jain and Goel, 2012;Strelec et al, 2019;Deblaere et al, 2019). In addition, there are three case reports in the literature of laparoscopic excision of a cystic mass from a unique location, namely the broad ligament (Shah et al, 2018;Trehan and Trehan, 2014;Chauhan et al, 2017).…”
Section: Discussionsupporting
confidence: 76%
“…Various terms have been used to describe what we now call ‘ACUMs’. These include ‘juvenile cystic adenomyoma’, 4,9,13–24 ‘isolated cystic adenomyoma’, 5,10–12,25,26 ‘uterine‐like mass’, 27,28 or ‘accessory uterine cavity’ 2,29,30 . In 2010, Acién et al.…”
Section: Nomenclaturementioning
confidence: 99%
“…Severe dysmenorrhoea is the commonest presenting symptom for women with ACUMs 3,7,12,13,15,23,34,35 . The pain can be central or ipsilateral to the side of the ACUM and may be accompanied by chronic pelvic pain 1,3,8,21,28,34 .…”
Section: Clinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation